Role of the RNA/DNA kinase Grc3 in transcription termination by RNA polymerase I. - Braglia, P; Heindl, K; Schleiffer, A; Martinez, J; Proudfoot, N (2010)
Transcription termination by RNA polymerase I in Saccharomyces cerevisiae is mediated by a 'torpedo' mechanism: co-transcriptional RNA cleavage by Rnt1 at the ribosomal DNA 3'-region generates a 5'-end that is recognized by the 5'-3' exonuclease Rat1; this degrades the downstream transcript and eventually causes termination. In this study, we identify Grc3 as a new factor involved in this process. We demonstrate that GRC3, an essential gene of previously unknown function, encodes a polynucleotide kinase that is required for efficient termination by RNA polymerase I. We propose that it controls the phosphorylation status of the downstream Rnt1 cleavage product and thereby regulates its accessibility to the torpedo Rat1.